Integrating Motivation, Time Management, and Metacognitive Strategies to Enhance EFL Academic Writing in Indonesian Higher Education - Sinarman Jaya (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2025)
Many EFL students in Indonesia struggle to organize ideas, build coherent arguments, and follow academic conventions, highlighting the need for strong self-regulated learning skills in motivation, time management, and metacognitive awareness. This study examined how these three factors interact to enhance students’ writing performance in Indonesian universities. Using a mixed-methods approach, data were collected from 110 students across three universities through questionnaires and semi-structured interviews. Quantitative results revealed significant positive relationships among motivation, time management, and metacognitive strategies, indicating that these components support each other in developing writing competence. The qualitative findings further explained this connection, showing that students were motivated but often influenced by grades and deadlines. They managed their time by dividing writing tasks into smaller steps and used metacognitive strategies such as planning, monitoring, and revising with teacher feedback. These findings emphasize the value of integrating motivation, time management, and metacognitive strategies in writing instruction to strengthen self-regulated learning and academic writing performance. The study provides useful implications for lecturers, curriculum designers, and higher education policymakers.